THE EFFECT OF WORK FROM HOME, ORGANIZATION COMMITMENT AND WORK DICIPLINE TO THE PERFORMANCE OF BAHASAKUINGGRIS EMPLOYEE DURING THE COVID-19 PANDEMIC - Siti Durotul Khasanah; Wachid Hasyim; Tri Wahyu Wirjawan (SEAN Institute, 2022)
The growing covid-19 virus in society, the government is urging employees to work from home to prevent and lessen the virus' spread. Therefore, employees do not require for going to the workplace and face to face. The aim of this study determined the effect of work from home, organization commitment and work dicipline to the performance of employees. This research. was held. at Bahasakuinggris in Pare, Kediri regency. Primary data is obtained by spreading questionnaires to 74 respondents. Data analysis was completed with SmartPLS 3.0 in this study. The research showed that the work from home variable was significant on the employee performance variable, then the organizational commitment variable was significant on the employee performance variable, and the work discipline variable was significant on the employee performance variable.